DETERMINAN YANG MEMPENGARUHI HARGA SAHAM - Nindi Sulistianingsih; Ismunawan (Bajang Institute, 2022)
This research was conducted to understand the rewards for issuinfinancial initiatives that are formed from profitability, liquidity, solvency and campaign initiatives on the interpretation of the forward-looking portfolios of automotive and molecular companies scheduled on the Indonesia Stock Exchange (IDX) during the 2016-2019 days. In this analysis, profitability initiatives are measured using Return On Assets (ROA), liquidity is measured using the Current Ratio (CR), solvency is measured using Debt to Equity Ratio (DER), and campaign initiatives are measured using Turn Asset Turn Over (TATO). In this analysis, the law of collecting a representative is used as part of this analysis, namely purposive sampling. The number of representatives participating in this analysis is 9 automotive and molecular companies scheduled on the Indonesia Stock Exchange (IDX) for a grace period of 4 days 2016-2019 which allows the benchmark to be set. The hint polemic method used in this analysis is Multiple Linear Regression Analysis. The results of the polemic examination of the analytical instructions show that the causes of profitability, liquidity, solvency and campaign initiatives have an impact on the interpretation of holdings. The results contained show that financial initiatives can strengthen the interpretation of a company's forward holdings